Co pozostaje po katastrofie? Narracje kobiet, które doświadczyły poronienia, w odniesieniu do koncepcji aktywnej nadziei i wzrostu posttraumatycznego - Kościańczuk, Marcela (Kultura-Społeczeństwo-Edukacja, 2025)
The article is based on qualitative research consisting of interviews with 21 women. The topics of the conversations were the changes they experienced after experiencing the loss of an important value for them, which was pregnancy (perceived by all respondents as the beginning of their children’s lives). Women pointed to the traumatic nature of this loss. In the text, I describe the changes indicated by women, consisting in the revaluation of certain worldviews, values and relationships, as well as the creation of their own narratives and certain ritual objects. I compare them with concepts related to reactions to trauma/disaster. The first of them (the concept of post-traumatic growth) refers to the individual experiences of individuals after experiencing the collapse of the former universe of values, and the second (the concept of active hope) refers to collective reactions to the ongoing climate catastrophe.